Strategies for Settler Decolonization: Decolonial Pedagogies in a Popular Music Analysis Course - Attas, Robin (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur, 2019)
Canadian institutions of higher education are grappling with decolonization, particularly with how to move beyond decolonial and settler colonial theory and the Truth and Reconciliation Commission of Canada’s Calls to Action to practical and specific strategies for meaningful change in the classroom. To that end, this paper offers a case study of a settler instructor’s process of decolonization in a popular music analysis course and describes a variety of methods for decolonizing course design and classroom activities. A discussion of how to apply and adapt the author’s methods for different courses, programs, and local contexts leads to critical reflection on the impact of these changes on student learning and their efficacy in terms of decolonization itself.